Rancang Bangun Sistem Informasi Online sebagai Media Promosi Trowulan - Rinabi Tanamal; Stephanus Eko Wahyudi (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Trowulan heritage is a cultural heritage which is one of the relics from the Majapahit Kingdom . A lot of effort has been done by the local community to preserve the culture and engraving surrounding communities. But these efforts have not been maximized, " The awareness " in Indonesia and International and yet need to know what more could be offered through the Trowulan site can be strengthened. Increased awareness of these needs should be done in an attempt to face free competition MEA. This research aims to design an online media website and integrated with social media. The result of interview and survey indicated that Trowulan need a website which collaborated all the Trowulan's information using combination of social media.  By implementing and sharing this website hopefully level of awareness in society can be reached as well as the economic life of the community around Trowulan may increase. Keywords— Cultural Heritage, HTML, Majapahit History, Tourism, Wordpress.